Impoliteness Strategies in Cruella Movie: Pragmatics Study - Meidina Sinrang Sjamsu Djohan; Ervina CM Simatupang (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze and indicate the types of impoliteness strategies and their meaning addressed by the characters in the movie Cruella. A descriptive qualitative method was employed in this study. The source of the data was from the movie Cruella in addition to the transcript of the movie. Data is collected through observation in several steps, including watching the movie, downloading the transcripts, identifying and marking the impoliteness strategies performed in the movie, and classifying each data with Culpeper's Impoliteness strategy. The data is analyzed by first describing the context of each conversation and then analyzing the data using Culpeper's impoliteness strategies. The result shows that there are five types of impoliteness strategies, including bald on record impoliteness (31%), positive impoliteness (23%), negative impoliteness (15%), off-record impoliteness (23%), withhold politeness (8%). In addition, there are two types of meaning literal meaning (69%) and non-literal meaning (31%).